2007
DOI: 10.3844/ajabssp.2007.276.283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat-Mineral Preparation from Fish Oil on Fatty Acid Content on Cow Milk

Abstract: 8-week-lasting investigation aimed at the assessment of the effect of fish oil application in the form of fat-mineral preparation (F-M) on fatty acid content in milk fat. The subject of this investigation were highly efficient dairy cows ( primiparous and multiparous). The cows were administered F-M containing fish oil (1% in dry mass of ration) which resulted in decreased level of shortchain fatty acids in milk fat and increased level of longchain fatty acids. There was recorded significant increase in isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Many workers reported a similar trend of decrease in carbohydrate (Venkataramana et al, 2006;Saradhamani and Selvarani, 2009). On the other hand, some other workers (Janeczek et al, 2007;Puoci et al, 2008;Logaswamy and Remia, 2009) reported that sublethal concentration of certain organophosphate pesticides caused glycogenolysis, which produced hyperglycemia in the African food fish Tilapia and the Indian catfish, Heteropneustes fossilis. Remia et al (2008) reported that the elevation of carbohydrates might be due to the stress induced by the insecticides as physiology of organisms with the help of corticosteroids.…”
Section: Resultsmentioning
confidence: 98%
“…Many workers reported a similar trend of decrease in carbohydrate (Venkataramana et al, 2006;Saradhamani and Selvarani, 2009). On the other hand, some other workers (Janeczek et al, 2007;Puoci et al, 2008;Logaswamy and Remia, 2009) reported that sublethal concentration of certain organophosphate pesticides caused glycogenolysis, which produced hyperglycemia in the African food fish Tilapia and the Indian catfish, Heteropneustes fossilis. Remia et al (2008) reported that the elevation of carbohydrates might be due to the stress induced by the insecticides as physiology of organisms with the help of corticosteroids.…”
Section: Resultsmentioning
confidence: 98%